Renewable-Based Treatment Solution of Reactive Blue 21 Dye on Fly Ash as Low-Cost and Sustainable Adsorbent - Gören, Ayşegül Yağmur; Kobya, Mehmet; Dolaz, Mustafa; Goren, Aysegul Yagmur (Elsevier, 2024)
This study investigated the removal of Reactive Blue 21 (RB 21) dye from aqueous solutions by adsorption, evaluating the waste fly ash (FA). The effects of the parameters, such as initial dye concentration (100-750 mg/ L), initial pH (2.0-8.0), adsorbent dose (1.0-4.0 g/L), and temperature (298-323 K) on the adsorption process were investigated. The optimum initial pH value was 2.0 for the highest RB21 dye removal (75.2 mg/g). At optimized conditions (pH 2.0, an adsorbent dosage of 1.0 g/L, a dye concentration of 750 mg/L, and an equilibrium time of 72 h), the highest adsorption capacity was found to be 105.2 mg/g. Moreover, the results of the kinetic studies fitted the pseudo-second-order kinetic model. Equilibrium data were best represented by the Langmuir isotherm model, with a maximum monolayer adsorption capacity of 103.41 mg/g at 323 K. Delta G0ads values were negative and varied from 11.64 to 9.50 kJ/mol in the temperature range of 298-323 K, the values of enthalpy (Delta Ho ads) and entropy (Delta So ads) of thermodynamics parameters were calculated as 37.62 kJ/mol and 86.67 J/mol K, respectively, indicating that this process was endothermic. Furthermore, the adsorbent costs for powdered activated carbon (PAC) and FA to remove 1 kg of RB 21 dye from aqueous solutions are calculated as 2.52 U.S. $ and 0.34 U.S. $, respectively. It is seen that the cost of FA is approximately 7.4 times lower than PAC. The results showed that FA, a low-cost industrial waste, was promising for the adsorption of RB 21 from aqueous solutions.
dolaz, mustafa/0000-0002-9684-5555
Keywords: Reactive Blue 21; Adsorption; Fly ash; Kinetics; Isotherm